Analisis Leverage, Firm Size, Intensitas Aset Dan Intensitas Persediaan Terhadap Tax Avoidance Pada Perusahaan Sektor Kimia Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2022 - Kaloko, Hairiah; Kustiawan, Memen; Fitriana (LPPM STIA Lancang Kuning Dumai, 2025)
This research aims to analyze the influence of Leverage, Firm Size, Fixed Asset Intensity, and Inventory Intensity on Tax Avoidance in chemical sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The phenomenon of tax avoidance which causes global losses of up to 427 billion USD per year and an ETR value that is lower than the applicable tax rate for several chemical sector companies is the background for this research. The research used a purposive sampling method with 10 companies for 4 years, analyzing 40 financial reports. Data analysis used panel data regression with the Random Effect Model (REM) based on the results of the Chow Test (Probability 0.8069>0.05) and the Hausman Test (Probability 0.5156>0.05). The research results show that Leverage has a significant positive effect (0.0000≤0.05), Firm Size and Fixed Asset Intensity have a significant negative effect (0.0000≤0.05 and 0.0366≤0.05), while Inventory Intensity has no significant effect (0.4299≥0.05). Simultaneously, the four variables have a significant effect with a coefficient of determination of 99.20%. These findings imply the importance of company characteristics in tax avoidance practices. Companies are expected to evaluate tax planning to produce optimal tax management, while future researchers can research other sectors for maximum results